Pseudomonas putida Stimulates Primordia on Agaricus bitorquis - Colauto, Nelson B.; Fermor, Terry R.; Eira, Augusto F. [UNESP]; Linde, Giani A. (Springer, 2016)
Casing layer is one step of Agaricus bisporus cultivation where there is a competitive environment with a high number of microorganisms and diversity interacting with mycelia. It is suggested that a minimal community of these microorganisms would be necessary to stimulate fructification. However, A. bisporus is not able to produce primordia in sterile casing layers or Petri dishes. Thus, the objective of this study was to characterize bacterial microbiota of casing layers from A. bisporus cultivation, isolate, identify and characterize the bacteria responsible for the stimulation of primordium and their action mechanism using Agaricus bitorquis as a primordium stimulation model. Bacterial and Pseudomonas spp. communities of different casing layers of A. bisporus cultivation were collected and quantified. It was concluded that Pseudomonas spp. corresponds to 75-85 % of bacterial population of the casing layers in A. bisporus cultivation and among those 12 % are Pseudomonas putida. Four biochemical assays were used to identify P. putida. In vitro primordium stimulation of living P. putida and non-living bacterial suspensions, after chemical or physical treatments, was tested using A. bitorquis as a primordium stimulation model. Primordium stimulation assay was registered by photographs, and micrographs of vertical cut of primordium were registered by scanning electron microscope. Interaction of living P. putida with A. bitorquis mycelia is capable of stimulating primordial instead of non-living bacterial suspensions. Stimulation of A. bitorquis primordia does not imply or is related to mycelial growth inhibition, but a hierarchical relation of primordium succession and development is suggested.